2013
DOI: 10.1247/csf.12026
|View full text |Cite
|
Sign up to set email alerts
|

UBC9 Regulates the Stability of XBP1, a Key Transcription Factor Controlling the ER Stress Response

Abstract: ABSTRACT. XBP1 is a key transcription factor regulating the mammalian endoplasmic reticulum (ER) stress response, which is a cytoprotective mechanism for dealing with an accumulation of unfolded proteins in the ER (ER stress). The expression of XBP1 is regulated by two different mechanisms: mRNA splicing and protein stability. When ER stress occurs, unspliced XBP1 mRNA is converted to mature mRNA, from which an active transcription factor, pXBP1(S), is translated and activates the transcription of ER-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Recent studies suggest that UBC9 may also impact on ER homeostasis; for example UBC9 protein regulates the expression of XBP-1 and the transcript's stability. 36 We confirmed that components of the UPR, including XBP-1, are upregulated by elevated levels of UBC9 (Online Figure VII) and UBC9 can directly target promoter elements involved in UPR activation (Online Figure VIIC and D). …”
Section: Resultssupporting
confidence: 68%
“…Recent studies suggest that UBC9 may also impact on ER homeostasis; for example UBC9 protein regulates the expression of XBP-1 and the transcript's stability. 36 We confirmed that components of the UPR, including XBP-1, are upregulated by elevated levels of UBC9 (Online Figure VII) and UBC9 can directly target promoter elements involved in UPR activation (Online Figure VIIC and D). …”
Section: Resultssupporting
confidence: 68%
“…From an evolutionary perspective, proteins such as Ubc-9 are suitable targets for pathogens because of their multifunctional role. These proteins, in addition to their E2 enzyme activity, could potentially function as biological chaperones, transcriptional coregulators, and regulators of signaling pathways (44)(45)(46)(47). The evolutionary conservation of Ubc-9 being at the center of many strategies to subvert host SUMO machinery is also mirrored in our observation regarding the mechanism of Ubc-9 degradation.…”
Section: Discussionsupporting
confidence: 57%
“…For example, XBP1(U) protein forms a complex with XBP1(S) protein, and undergoes rapid proteasome degradation under non-stress conditions, which shuts off the transcription of target genes of XBP1(S) during the recovery phase of ER stress [48]. It was also reported that the small ubiquitin-like modifier (SUMO) conjugase ubiquitin-conjugating enzyme 9 (UBC9) specifically binds to XBP1(S) and increases its stability [49]. …”
Section: Unfolded Protein Responses In Mammalsmentioning
confidence: 99%